Polymorphisms in the Myostatin-1 gene and their association with growth traits in Ancherythroculter nigrocauda - 孙艳红 李清 王贵英 祝东梅 陈见 李佩 童金苟 (Chinese journal of oceanology and limnology, 2017)
Myostatin （MSTN） is a member of the transforming growth factor-β gene superfamily that negatively regulates skeletal muscle development and growth. In the present study, partial genomic fragments of Myostatin-1 （MSTN-1） in two commercial hatchery populations of Ancherythroculter nigrocauda, an economically important freshwater fish, were screened for single nucleotide polymorphisms （SNPs） and then genotyped by direct sequencing of PCR products. Five SNPs were identified in intron 1 and exon 2, including a non-synonymous mutation causing an amino acid change （Val to Ile） at position 180. Association analyses based on 300 individuals revealed that the g. 1129T〉C SNP locus was significantly associated with total length （TL）, body length （BL）, body height （BH） and body weight （BW） in 6- and 18-month-old populations, while the g. 1289G〉A locus was significantly associated with BH and BW in the 6-month-old population. Haplotype analyses revealed that fish with the genotype combinations TC/TC or TC/GA showed better growth performance. Our results suggest that g.l129T〉C and g.1289G〉A have positive effects on growth traits and may be candidate gene markers for marker-assisted selection in A. nigrocauda.